Neuropsychiatric Sequelae in Adolescents With Acute Synthetic Cannabinoid Toxicity - Anderson, Sarah Ann R. (Pediatrics, 2019)
BACKGROUND AND OBJECTIVES: Adolescents represent the largest age group that presents to emergency departments (ED) for synthetic cannabinoid (SC) toxicity; however, the neurotoxic effects of acute SC exposures in this group are understudied. Our aim was to characterize the neuropsychiatric presentation of adolescents with SC-related exposure in the ED compared with those with traditional cannabis exposure. METHODS: A multicenter registry of clinical information prospectively collected by medical toxicologists (Toxicology Investigators Consortium Case Registry) was reviewed for adolescents presenting to the ED after SC or cannabis exposure from 2010 through 2018. Associations were measured between drug exposures and neuropsychiatric symptoms and/or signs. Exposures were classified into 4 groups: SC-only exposure, SC-polydrug exposures, cannabis-only exposure, and cannabis-polydrug exposures. RESULTS: Adolescents presenting to the ED with SC-only exposure (n = 107) had higher odds of coma and/or central nervous system depression (odds ratio [OR] 3.42; 95% confidence interval [CI] 1.51–7.75) and seizures (OR 3.89; 95% CI 1.39–10.94) than those with cannabisonly exposure (n = 86). SC-only drug exposure was associated with lower odds of agitation than cannabis-only exposure (OR 0.18; 95% CI 0.10–0.34). In contrast, the group with SC-polydrug exposures (n = 38) had higher odds of agitation (OR 3.11; 95% CI 1.56–7.44) and seizures (OR 4.8; 95% CI 1.80–12.74) than the cannabis-polydrug exposures group (n = 117). CONCLUSIONS: In this multisite cohort of US adolescents assessed in the ED, SC exposure was associated with higher odds of neuropsychiatric morbidity than cannabis exposure providing a distinct neurospychiatric profile of acute SC toxicity in adolescents.